ANGIOGENIC BIOMARKERS IN THE PREDICTION AND DIAGNOSIS OF PREECLAMPSIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Preeclampsia (PE) remains a major cause of maternal and perinatal morbidity and mortality globally. Recent research has focused on the imbalance between angiogenic and antiangiogenic factors—particularly soluble fmslike tyrosine kinase1 (sFlt1) and placental growth factor (PlGF)—as potential biomarkers for early prediction and diagnosis of PE. To review and synthesize current evidence on the clinical performance of sFlt1, PlGF, and the sFlt1/PlGF ratio in predicting, diagnosing, and managing preeclampsia across different gestational stages and populations.